Establishment of The Law On The Seizure of Assets Resulting From Money Laundering Based On Fair Law Enforcement In Indonesia - Sitompul, Ariman; Hasibuan, Edi Saputra (SASI, 2023)
Introduction: The realization of Parliament's desire to support asset seizure efforts, currently there is a discourse to regulate the seizure of assets resulting from criminal offenses in a separate law. The proposal to form a law on the expropriation of assets resulting from criminal acts is seen in the agreement to include a draft law on the expropriation of assets resulting from criminal acts in the National Legislation 2009-2014.Purposes of the Research: The purpose of this study is to explain the paradigm that the importance of the establishment of asset seizure laws in money laundering.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: The urgency of establishing a special asset seizure law for money laundering is an inadequate mechanism. Adequate mechanisms in asset seizure efforts are expected to use the mechanisms contained in the UNCAC so that asset seizure in Indonesia will run effectively.